Magnetic Nanopolymer: Applications and Challenges in Medical Imaging and Theranostics - Gizachew Diga (International Journal of Crystalline Materials, 2025)
Biopolymers are valuable complex materials. They attract attentions of many scientists, engineers and medical professionals’ for application research. In this research, an assessment of emerging Nanopolymers including magnetic nanopolymer is focused. Hence, sources, magnetic properties, and biomedical application of such polymers are given attention. As ordinary polymers, nano sized biopolymers are visualized as natural and synthetic polymers. However, more emphasis is given to green synthesized magnetic polymer, particularly magnetic Chitosan nanoparticles. Hence, systematic descriptions of nanosized biopolymers, it synthesis procedure, and characterization methods is presented. In this regard, the green synthesis of Chitosan nano particles is illustrated. Hence, the effect of magnetic field and light on the crystallographic bond formation and structure of Chitosan nanoparticles is overseen. Properties such biodegradations, biocompatibility, photo catalytic activity, sensitivity, and fluorescence of magnetic nanopolymer is also reviewed. The biomedical applications of such nanosized polymers are presented by enumerating its nanobiophysical properties. More importantly drug delivery, medical imaging, and theranostics are discussed as a core function of magnetic polymer nanoparticles. Due to its peculiar physio - chemical properties, Chitosan is preferred in biomedical applications as diagnosis, cell/tissue imaging, therapy, wound healing, and nano carrier of drug delivery. Moreover, challenges associated with drug delivery, imaging and theranostics procedures using nanopolymer is presented.
Keywords: Chitosan Nanoparticles; Magnetic Nanopolymers; biomedical applications; drug delivery; green synthesis